PROFIL TUGAS PERKEMBANGAN MANULA DI JORONG TAMBUN IJUK KOTO TANGAH BATU HAMPA KECAMATAN AKABILURU KABUPATEN LIMA PULUH KOTA - Riyani, Fidha; Kasih, Fitria; Gusneli, Gusneli (Bimbingan dan Konseling, 2013)
The problem in this study is: What is the profile assignment elderly development in Tambun Jorong Ijuk Koto Tangah Stone Marijuana District Akabiluru District Fifty Cities. This study aimed to describe: 1) seniors developmental task of adjusting to decreasing physical strength and health 2) seniors developmental task of adjusting to the death of a spouse. This research is a descriptive study describes a real situation. The populations are 36 people. Sampling in this study uses total sampling technique because when the subject is less than a hundred, better grab all the samples. Data collection tool used was a questionnaire, while the technique analyzed using percentages. The results obtained showed that the task of development of seniors in adjusting to decreasing physical strength and health are at the unfavorable category as much as 36.11% and seniors developmental task of adjusting to the death of a spouse is in the unfavorable category as much as 41.66%. Based on these results it can be concluded that the profile of the development tasks can be categorized as poor seniors. Recommended for seniors to be able to add insight or knowledge about the developmental tasks that must be accomplished when entering old age and to the families of seniors in order to pay attention to the needs of seniors are required to achieve development tasks.